Traditional furniture. The effects from the introduction of new methods and materials / Alfian Gunawi - Gunawi, Alfian (1992)
Malaysian traditional furniture has its own characteristics and values. Despite all of the discrepancies in determining the agreed form of 'traditional furniture' several opinions and ideas should be analyzed thoroughly. This is because there is no standard guidelines or rule to be used as a standard scale in identifying what is 'Malay Traditional Furniture'. Within that study the form of approach should be look as furniture design in the general term. 'Traditional' as described by the Oxford Dictionary stated as something to be based on or obtained by tradition. 1 'Furniture' then was described as moveable contents of building or room, accessories far example handles or locks on door. However from the term stated by the Dept of Etanology, the meaning of traditional furniture must comply to any furniture made in the traditional style and carves with the traditional motifs without changing the category of design.